FACTOR COGNITIVE DISSONANCE IN PEDAGOGICS PHYSICAL EFFORT AND MOTOR ACTIVITIES - Вржесневский, І. І.; Ракитина, Т. І.; Пахомов, В. І.; Дейнеко, І. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article deals with the problem of cognitive dissonance in the physical effort of physical activity as a factor influencing the process of physical training of students studying youth. The aim of the article is to determine the possible manifestations and consequences of cognitive dissonance arising from students in relation to employment and education graphically own corporeality